Magneto-optical evidence for a gapped Fermi surface in underdoped YBa 2Cu3O6+x - Rigal, L.B.; Schmadel, D.C.; Drew, H.D.; Maiorov, B.; Osquiguil, E.; Preston, J.S.; Hughes, R.; Gu, G.D. (American Physical Society, 2004)
Fil: Maiorov, B. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina